Pengaruh Motivasi Kerja dan Iklim Organisasi Terhadap Kinerja Pegawai Pada Dinas Perdagangan Kabupaten Mamuju - Barung, Rachmat; Ramli S, Ramli S (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
Human resources are the only organizational assets that breathe or live besides other assets that do not breathe or are material in nature such as capital, buildings, office equipment machines, inventory, and so on. The uniqueness of human resource assets requires management that is different from other assets, because these assets have thoughts, feelings and behaviors, so that if managed properly they can actively contribute to the progress of the institution. Researchers used the method of multiple linear regression analysis with the help of the SPSS (Statistical Product Service Solution) computerized program. The results of the partial test using multiple linear regression show that the motivation variable has a significant value of 0.004 <0.05 and the organizational climate variable has a significant value of 0.000 <0.05, while the simultaneous test shows an Fcount value of 12.094 with a significant level of 0.000. Thus it is stated that motivation and organizational climate have a significant effect on employee performance at the Mamuju Regency Trade Service Office. The organizational climate variable that most dominantly influences employee performance at the Mamuju District Trade Office with the highest organizational climate variable coefficient value of 0.719 with the lowest significant level of 0.000, when compared to the motivational variable coefficient value of 0.539 with a significant level of 0.004.